Understand And Interpretate:Article 24 Verse (1) Letters Dregulation Of The Minister Of Health Of The Republic Of Indonesia Number 38 Year 2016 Concerning Organ Transplantation Concerning Written Approval Of Human Body Transplantation With Notary Asset. - Habib Adjie (Institute of Computer Science (IOCS), 2021)
In the stages of transplanting human organs from prospective donors to recipients, they must first fulfill the provisions contained in Article 24 Paragraph (1) letter d and Article 32 of the Regulation of the Minister of Health of the Republic of Indonesia Number 38 of 2016 concerning Organ Transplantation Regarding Approval for Human Organ Transplantation, namely there is a written statement with a notary deed. That in the transplant there is no indication of buying and selling or any other special agreement. The sentence (phrase) in the article is